LIMBAH KULIT BUAH KESUMBA (BIXA ORELLANA L.) SEBAGAI ALTERNATIF INDIKATOR ASAM BASA ALAMI (IABA) - Ria Nurindah, Friyatmoko Wahyu K., Dian Rahmawardani,Mekar Sari Dewi, dan Elfan Rosyadi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research aims at revealing the process of making the indicator of acid basesfrom the rind of kesumba fruit (Bixa orellana L.), the changes of colour it produces, thebest solvent among ethanol, acetone, and ethyl acetate solvents used in the making ofacid base indicator and the way to use the indicator.The research was conducted in the analysis chemistry laboratory of the Faculty ofMathematics and Natural Sciences of Yogyakarta State University from February up toMay, 2010. the research methods include producing the acid base indicator from thepowder made of the rind of kesumba fruit and making pH route.The results of the research are 1). pH indicator of acid base can be made by usingthe pigment contained in the rind of kesumba fruit. The liquid indicator is made bydissolving the clean and thinly sliced rind kesumba fruit with solvent. The solution isleft for a night in order that all pigments can dissolve perfectly. The extract is then keptin a refrigerator. 2). The change of colour in the solvent that has been tested by using theliquid acid base pH indicator can be observed so that the pH route can be produced. ThepH route can be used by matching the change of colour in the solvent that has beentested by using the liquid indicator so that the pH solvent can be found. 3). The acetonesolvent proves to be the best solvent in the making of acid base indicator from the rindof kesumba fruit powder. The pH route of the indicator is: pH 2 – 7: pale yellow; pH 8 – 10: light brown; pH 11 – 12 : dark brown. 4). The liquid indicator is used by expelling 2 – 3drops of indicator into the small portion of the solvent and the change of colour isobserved. It the indicator shows pale yellow, the solvent is acid, whereas pH over 10 isindicated as dark brown in the indicator.Key words : kesumba, pH indicator, pH